Palaeoclimate and human occupation in southeastern arid Australia. (1st May 2017) - Hughes, Philip J.; Sullivan, Marjorie E.; Hiscock, Peter
Abstract: This review focuses on the relationships between palaeoenvironmental change and prehistoric occupation in the driest part of the Australian arid zone. Palaeoclimatic evidence from the last ∼60 ka identified fluctuating periods of wet and dry conditions during the late Pleistocene and Holocene. For most of this period conditions were arid, including during the Holocene, and maximum aridity occurred at the LGM which peaked at ∼21 ka. Maximum wetness occurred before ∼45 ka, at ∼33–31 ka and episodically during the deglaciation between ∼18 and 11 ka. The pre-LGM archaeological record is extremely sparse but records from the LGM through to the mid Holocene show people occupied the dunefields and stony plains during prolonged wet periods in the deglaciation and largely abandoned them during drier phases, retreating to better-watered refuges. Human occupation in dunefields from the LGM through to the mid Holocene can be used as a proxy for past climates. From the late Holocene changes in settlement patterns were made possible by the social, economic and technological adaptations which allowed people to occupy what became an increasingly harsh environment. These reconstructions were facilitated by discoveries in the Roxby dunefield of buried stratified layers of stone artefacts in dune sands, dated by single–grain luminescence analyses. These discoveries indicate the possibility that hitherto unreported cultural sequences, potentially dating back to >50 ka, may be present in many Australian dunefields. Highlights: Australian arid zone archaeological occupation shows close links with palaeoclimate in the late Pleistocene and Holocene. Geoarchaeological investigations in the Roxby dunefield provided details on use of the sandridge deserts then. The quartz sandridges on which many archaeological sites occur enabled optical dating of occupation layers. Buried artefact layers match periods palaeoclimate reconstructions show to have been wetter. In similar sand deserts archaeological occupation can be used as a proxy for wetter climates.